2022
DOI: 10.3390/cancers14061431
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding in Gynecologic Cancer as a Marker for Poor Survival: A Systematic Review and Meta-Analysis of the Perspectives of Epithelial–Mesenchymal Transition

Abstract: This study aimed to assess the prognostic significance, assessment methods, and molecular features of tumor budding (TB). A literature search of Medline, EMBASE, Cochrane Library, and eleven cohort studies (seven cervical and four endometrial cancers) was conducted. Three assessment methods for TB involving 2009 patients were collected and constituted in the analysis. Our meta-analysis showed that TB was a marker of poor survival, regardless of the cancer origin site or assessment method (overall survival: haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
14
0
3
Order By: Relevance
“…Moreover, we directly compared several ITB assessment methods; subsequently, we revealed that ITB-total had a superior prognosis predictive power compared with TB-ITBCC, TB-YN, and ITB×400. TB-YN is simple and highly reproducible [ 8 ]; however, TB mimickers, such as macrophages, tangentially sectioned tumor glands, and apoptotic tumor cells, can be misinterpreted as TB cells. Using TB-ITBCC and TB×400, the number of TBs was counted in only one hotspot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we directly compared several ITB assessment methods; subsequently, we revealed that ITB-total had a superior prognosis predictive power compared with TB-ITBCC, TB-YN, and ITB×400. TB-YN is simple and highly reproducible [ 8 ]; however, TB mimickers, such as macrophages, tangentially sectioned tumor glands, and apoptotic tumor cells, can be misinterpreted as TB cells. Using TB-ITBCC and TB×400, the number of TBs was counted in only one hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the tumor microenvironment (TME) has been shown to play a key role in improving treatment or cancer management [ 4 ]. Among the TME factors, tumor budding (TB) [ 5 , 6 , 7 , 8 ], cancer-associated fibroblasts [ 9 ], tumor-infiltrating immune cells [ 10 , 11 , 12 ], and tumor endothelial cells [ 4 , 12 ] are prognostic markers of various solid cancers. In addition, some factors, such as TB [ 5 , 13 ], peritumoral inflammation [ 14 , 15 , 16 , 17 ], and the degree [ 15 , 16 , 18 ] or features [ 19 , 20 , 21 ] of fibrosis, are measurable without additional immunohistochemistry, as semi-quantitative or three-tier scoring systems have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have noted the high correlation between TB status and cancer progression [ 5 , 6 , 7 , 16 ]. Because tumor progression results from the interaction between tumor cells and the TME, insights into biological TB can provide potential tools for cancer management [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tumor budding (TB) histology has become a critical biomarker for several solid cancers, including colorectal cancer, head and neck cancer, pancreatic cancer, etc. [ 2 , 3 , 4 , 5 , 6 ]. In addition, we previously showed that TB status is a potential independent prognostic factor and can strongly interfere with CC treatment strategies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…TB is part of the tumor microenvironment (TME) and is related to epithelial–mesenchymal transition (EMT) ( 7 , 8 ). The prognostic significance of TB has been explored in solid cancers ( 7 ), such as colon cancer ( 9 , 10 ), gastric cancer ( 11 , 12 ), gynecologic cancer ( 13 , 14 ), and pancreatic cancer ( 15 ). Moreover, the prognostic significance of TBs and an association with EMT have also been explored in patients with lung cancer ( 16 25 ), but it has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%